2013
DOI: 10.1016/j.fra.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Radical scavenging activity of steviol glycosides, steviol glucuronide, hydroxytyrosol, metformin, aspirin and leaf extract of Stevia rebaudiana

Abstract: a b s t r a c tIntroduction: Reactive oxygen species (ROS), generated in many bioorganic redox processes, are the most dangerous by-products in the aerobic environment. The aim of this study was to compare the in vitro antioxidant activity of some chemical compounds and leaf extract of Stevia rebaudiana as natural antioxidant. Methods: The radical scavenging activity of ascorbic acid, quercetine, stevioside (ST), rebaudioside A (Reb A), steviol glucuronide (SVglu), glucose, sucrose, hydroxytyrosol, metformin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
3
19
0
3
Order By: Relevance
“…The efficacy of the extracts from the leaves was higher than that of stems, while the capacity of stevioside and rebaudioside A, the most abundant sweeteners found in stevia, was much lower through ORAC (ranging from 2.1-10.7%). Furthermore, these data confirm the previous findings from Hajihashemi group (Hajihashemi & Geuns, 2013), who also found a better ROS scavenging capacity for crude extracts.…”
Section: Resultssupporting
confidence: 91%
“…The efficacy of the extracts from the leaves was higher than that of stems, while the capacity of stevioside and rebaudioside A, the most abundant sweeteners found in stevia, was much lower through ORAC (ranging from 2.1-10.7%). Furthermore, these data confirm the previous findings from Hajihashemi group (Hajihashemi & Geuns, 2013), who also found a better ROS scavenging capacity for crude extracts.…”
Section: Resultssupporting
confidence: 91%
“…Literature sources about Fe(III)‐photocatalysis indicated citric acid can combine with iron to form Fe(III)‐citrate complexes, which can photo‐oxidize under UV light to generate HO• (Wu and Deng ; Chen and others ). Rebaudioside A has been reported to be an excellent HO• scavenger (Hajihashemi and Geuns ). It is hypothesized that the HO• generated from Fe(III)‐citrate complex can accelerate the degradation of rebaudioside A.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Hajihashemi and Geuns [58] hypothesized that, due to the high content of sugars present in the SGs, these presented their high antioxidant capacity; however, the results showed that this did not occur.…”
Section: Discussionmentioning
confidence: 99%